2002
DOI: 10.1291/hypres.25.553
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Renal Artery Stenosis in Patients Undergoing Cardiac Catheterization.

Abstract: Renal artery stenosis (RAS) is recognized as a major co-morbid condition for patients with cardiovascular disease. Although the prevalence of RAS in Western countries has been reported as 13.5-18% in patients with suspected coronary artery disease (CAD) undergoing coronary angiography, there is little information available about the prevalence of RAS in Asian populations, which are less susceptible to atherosclerosis. To evaluate the prevalence of RAS in Japanese patients suspected of cardiovascular disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 31 publications
2
32
1
1
Order By: Relevance
“…Thus, our results for the rate of RAS in Japanese patients with PAD are similar to those found in previous studies. Yamashita et al 18 reported that RAS also occurs frequently in Japanese patients with CHD and that the prevalence of RAS is higher in patients with established CHD: 10, 9 and 19% in patients with 1-, 2-and 3-vessel disease, respectively. Our results suggest that the prevalence of RAS in patients with PAD is higher than that in patients with established CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results for the rate of RAS in Japanese patients with PAD are similar to those found in previous studies. Yamashita et al 18 reported that RAS also occurs frequently in Japanese patients with CHD and that the prevalence of RAS is higher in patients with established CHD: 10, 9 and 19% in patients with 1-, 2-and 3-vessel disease, respectively. Our results suggest that the prevalence of RAS in patients with PAD is higher than that in patients with established CHD.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, race/ethnicity (Hispanic vs African American) was an independent predictor of lower RAS prevalence in the second group. 27 Yamashita et al 28 reported that significant RAS among Japanese patients with suspected CAD had a prevalence of 7%. Our study shows that the prevalence of significant RAS in Iranian patients is very similar to that reported in other countries (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…20,[23][24][25] Attention has also been paid to the role of ethnicity in the prevalence of RAS. [26][27][28] This study aims to assess the prevalence of RAS in patients with hypertension and suspected CAD who are candidates for coronary angiography. This research further aims to clarify RAS predictors and to estimate prevalence based on the number of risk factors in patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 5% to 22% of elderly patients with CKD have coexisting renal artery stenosis. Renal artery stenosis is also a risk factor for CVD, and the complication rate for atherosclerotic disease in other organs is high 7,[36][37][38] . In the primary prevention of CVD, carotid artery findings and renal artery stenosis should be noted.…”
Section: Peripheral Arterial Disease (Pad) and Abdominal Aortic Aneurmentioning
confidence: 99%